Politicking for Postwar Modernism: The Architectural Research Group of Ottawa and Montreal - Valen, Dustin (Urban History Review / Revue d'histoire urbaine, 2017)
issued: 2017-21-00

Conforme? Une histoire sociale du vêtement masculin chez les élites de Montréal, 1837-1918 - Villeneuve, Louis-Étienne (Université du Québec à Trois-Rivières, 2016)
Keywords: Bourgeoisie; Vêtements

Premiers regards sur les oeuvres d'art de la CSDM: Une histoire de commandes, de courants artistiques, de matérialités, d'intégrations - Doucet, Danielle (ARQ - Architecture Québec, 2015)
Number: 172

A Locational History of Fashion in Montréal - Sark, Katrina; Bélanger-Michaud, Sara Danièle (University of Chicago Press, 2016)
Keywords: Cinéma; Confection; Costume; Expositions; Musique; Musée McCord; Musée des Beaux-Arts; Musées; Vêtements

The Goode House (The Westmount Historian, 2021)
Number: 2
Keywords: Conservation; Famille; Jardins; Patrimoine

Loisirs dansants de la bourgeoisie anglo-montréalaise. Transformation et persistance des lieux de pratique, 1870–1940 - Roquigny, Peggy (Urban History Review / Revue d'histoire urbaine, 2011)
issued: 2011-23-00
Keywords: Anglophones; Bourgeoisie; Danse

Design and Innovation in Montreal through the 1960s and the 1970s - Sharman, Lydia Ferrabee (Material History Review / Revue d’histoire de la culture matérielle, 2005)
issued: 2005-21-00
Keywords: Expositions; Place Ville-Marie; Transport en commun

Manly Smokes: Tobacco Consumption and the Construction of Identities in Industrial Montreal, 1888-1914 - Rudy, Robert Jarrett (Université McGill, 2001)
This dissertation explores the cultural practice of smoking and its connection to social relations from the beginning of cigarette mass production in Montreal in 1888 to the First World War. It uncovers the norms of smoking etiquette and taste, their roots in gender, class and race relations and their use in reproducing these power relationships. It argues that these prescriptions reflected and served to legitimize beliefs about inclusion, exclusion and hierarchy that were at the core of nineteenth century liberalism. Liberal ideals of self-control and rationality structured the ritual of smoking: from the purchase of tobacco; to who was to smoke; to how one was supposed to smoke; to where one smoked. These prescriptions served to normalize the exclusion of women from the definition of the liberal individual and to justify the subordination of the poor and cultural minorities. Furthermore, even while these prescriptions were at their height, an emergent group of beliefs began to recast notions of respectable smoking around new ideals of speed and ungendered universality. This challenge was not only part of the transition from bourgeois to mass consumption, it was the roots of a transformation of the liberal order in the years previous to the First World War.
Keywords: Tabac

Créer en récupérant: les enjeux de la récupération des textiles dans le design de mode québécois depuis 1980 - Simard, Isabelle (Université Laval, 2002)
Keywords: Textile; Vêtements

Fashioning Identity: The Hostesses of Expo 67 - Kirkman (Université Concordia, 2011)

A Little On the Wild Side: Eaton's Prestige Fashion Advertising Published in the Montreal Gazette, 1952-1972 - Bosnitch, Katherine (Université Concordia, 2000)
Keywords: Eaton; Magasins; Montreal Gazette; Publicité